Comparative Evaluation of Efficacy of Three Different Herbal Toothpastes on Salivary Alkaline Phosphatase and Salivary Acid Phosphatase - A Randomized Controlled Trial - Khairnar, Mahesh (J Clin Diagn Res, 2016)
INTRODUCTION: Very few researches in the past have tried to evaluate the effect of herbal toothpaste on saliva and salivary constituents like alkaline phosphatase and acid phosphatase which play an important role in maintaining oral health. AIM: To evaluate and compare the effect of three different herbal toothpastes on Salivary Alkaline Phosphatase (ALP) and salivary Acid Phosphatase (ACP). MATERIAL AND METHODS: The present study was a preliminary study conducted among 45 dental students (15 subjects in each group) in the age group of 19-21 years. Subjects in each group were randomly intervened with three different herbal toothpastes respectively (Group A – Patanjali Dant Kanti, Group B - Himalaya Complete Care and Group C – Vicco Vajradanti). Unstimulated saliva sample were collected before and after brushing and salivary ACP and salivary ALP levels were assessed at an interval of one week each for a period of four weeks starting from day one. Compiled data was analyzed using chi square test, paired t-test and ANOVA based on the nature of the obtained data. RESULTS: All the three toothpastes showed significant (p<0.001) reduction in ACP and ALP levels at each interval. For patanjali toothpaste, the mean reduction was in the range of 2.55 – 2.62 IU/L for ACP and 2.94 – 2.99 IU/L for ALP. For Himalaya toothpaste, the mean reduction was in the range of 1.39 – 1.47 IU/L for ACP and 1.55 – 1.61 IU/L for ALP. For Vicco toothpaste, the mean reduction was in the range of 2.46 – 2.50 IU/L for ACP and 2.64 – 2.77 IU/L for ALP. Patanjali and Vicco toothpaste were significantly effective in reducing the levels of salivary ACP and ALP more than Himalaya toothpaste (p<0.05). CONCLUSION: Herbal toothpastes, especially Dant Kanti and Vicco Vajradanti, showed significant reduction in levels of ACP and ALP resulting in overall improvement towards the oral health.